The creative economy and the triple transition - Pratt, Andy C. (Frontiers in Communication, 2026)
This study examines the role of culture in the Triple Transition, a task that it argues requires rethinking how we understand culture. It argues that these questions rest on a further problematic relationship of culture and development, challenging the normative idea that culture is an instrumental communication tool that facilitates development. The study argues that we need to appreciate culture in development, namely as a system of practices, values (economic, environmental, social, and cultural), and institutions that are embedded in places and times. We review the impact on, and of, the culture and creative sector in each dimension of the triple transition: digital, social, and environmental. The review of findings across the areas of the triple transition (digital, social, and environmental) suggests that culture plays an intrinsic role in development, better described as a driver of change rather than a bystander.